2012
DOI: 10.1159/000332000
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatical Assistance of Selecting Anti-HIV Therapies: Where Do We Stand?

Abstract: In this opinion statement, we give a critical synopsis of the state-of-the-art of bioinformatic HIV resistance analysis and point out what we consider to be challenges and perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Rules-based systems or systems that predict the phenotypic resistance factor for each drug, like geno2pheno [resistance] (virtual phenotype), are most frequently used. Also discussed by Lengauer [33] in this issue, one speculated reason for this ambiguous acceptance is that the mechanisms of how the bioinformatic systems choose the optimal treatment are sometimes not comprehensible. In many cases this could be prevented by an optimized presentation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Rules-based systems or systems that predict the phenotypic resistance factor for each drug, like geno2pheno [resistance] (virtual phenotype), are most frequently used. Also discussed by Lengauer [33] in this issue, one speculated reason for this ambiguous acceptance is that the mechanisms of how the bioinformatic systems choose the optimal treatment are sometimes not comprehensible. In many cases this could be prevented by an optimized presentation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one aim of this study was to explore the perspectives of virtualizing the phenotype vector by providing a computational procedure that estimates the phenotype vector based on the V3 loop sequence of the virus (see also [47]). We developed a method for predicting the phenotype vector that is based on the V3 loop sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this approach has been supplemented with machine learning techniques 70. To influence patient treatment molecular modeling will have to work alongside these and other novel bioinformatics approaches71 and eventually be incorporated into existing clinical tools. A comparison of decision support systems has found that machine learning techniques outperform traditional rule based systems unless additional patient attributes are considered 72.…”
Section: The Future Now: Genotypic Assays and Hivmentioning
confidence: 99%